Association of miR-149 T>C and miR-196a2 C>T polymorphisms with colorectal cancer susceptibility: a case-control study - Bayramov, Bayram; Bayramov, Nuru; Aslanov, Hazi; Karimova, Nigar; Gasimov, Karim; Shahmuradov, Ilham; Reißfelder, Christoph; Yagublu, Vugar (Biomedicines, 2023)
The principal aim of the current study was to investigate the relationship between miR-149 T>C (rs2292832) and miR-196a2 C>T (rs11614913) small non-coding RNA polymorphisms and the risk of developing CRC in the Azerbaijani population. The study included 120 patients diagnosed with CRC and 125 healthy individuals. Peripheral blood samples were collected from all the subjects in EDTA tubes and DNA extraction was performed by salting out. Polymorphisms were determined using the polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) method. While comparing without gender distinction no statistical correlation was found between the heterozygous TC (OR = 0.66; 95% CI = 0.37-1.15; p = 0.142), mutant CC (OR = 1.23; 95% CI = 0.62-2.45; p = 0.550), and mutant C (OR = 1.03; 95% CI = 0.72-1.49; p = 0.859) alleles of the miR-149 gene and the CT (OR = 1.23; 95% CI = 0.69-2.20; p = 0.485), mutant TT (OR = 1.29; 95% CI = 0.67-2.47; p = 0.452), and mutant T (OR = 1.17; 95% CI = 0.82-1.67; p = 0.388) alleles of the miR-196a2 gene and the risk of CRC. However, among women, miR-149 TC (OR = 0.43; 95% CI = 0.19-1.01; p = 0.048) correlated with a reduced risk of CRC, whereas miR-196a2 CT (OR = 2.77; 95% CI = 1.13-6.79; p = 0.025) correlated with an increased risk of CRC. Our findings indicated that miR-149 T>C (rs2292832) might play a protective role in the development of CRC in female patients, whereas the miR-196a2 (rs11614913) polymorphism is associated with an increased risk of CRC in women in the Azerbaijani population, highlighting the importance of gender dimorphism in cancer etiology.